Natural Compounds and Autophagy: Allies Against Neurodegeneration - Stacchiotti, Alessandra; Corsetti, Giovanni (Frontiers in Cell and Developmental Biology, 2020)
Prolonging the healthy life span and limiting neurological illness are imperative goals in gerontology. Age-related neurodegeneration is progressive and leads to severe diseases affecting motility, memory, cognitive function, and social life. To date, no effective treatments are available for neurodegeneration and irreversible neuronal loss. Bioactive phytochemicals could represent a natural alternative to ensure active aging and slow onset of neurodegenerative diseases in elderly patients. Autophagy or macroautophagy is an evolutionarily conserved clearing process that is needed to remove aggregate-prone proteins and organelles in neurons and glia. It also is crucial in synaptic plasticity. Aberrant autophagy has a key role in aging and neurodegeneration. Recent evidence indicates that polyphenols like resveratrol and curcumin, flavonoids, like quercetin, polyamine, like spermidine and sugars, like trehalose, limit brain damage in vitro and in vivo. Their common mechanism of action leads to restoration of efficient autophagy by dismantling misfolded proteins and dysfunctional mitochondria. This review focuses on the role of dietary phytochemicals as modulators of autophagy to fight Alzheimer’s and Parkinson’s diseases, fronto-temporal dementia, amyotrophic lateral sclerosis, and psychiatric disorders. Currently, most studies have involved in vitro or preclinical animal models, and the therapeutic use of phytochemicals in patients remains limited.